GENERALITY AND DIFFERENCES BETWEEN SITUATION PROBLEMS AND CASE METHODS - Safarova Nafisa Sulaymonovna; Karimov Javokhir Sobirzoda (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Situational problem-based learning, its essence. Pedagogical research on PBL and Case study methods, their results. Strengths and weaknesses of situational problem-based teaching. The essence of the content of the Case study, the peculiarities and weaknesses of the Case study, the similarities and differences between PBL and Case.